Contrasting Effects of Lithium Chloride and CB1 Receptor Blockade on Enduring Changes in the Valuation of Reward - Hernandez, Giovanni; Bernstein, David; Schoenbaum, Geoffrey; Cheer, Joseph F. (Frontiers in Behavioral Neuroscience, 2011)
When an organism has been trained to respond for a reward, its learned behavior can be characterized as goal-directed or habitual based on whether or not it is susceptible to reward devaluation. Here, we evaluated whether instrumental responding for brain stimulation reward (BSR) can devalued using a paradigm traditionally used for natural rewards. Rats were trained to lever press for BSR. Subsequently, BSR was paired with either lithium chloride (LiCl, 5 mg/kg, i.p), a pro-emetic, or AM251, a CB1 receptor antagonist (3 mg/kg, i.p.). Pairings of BSR with these two compounds or their respective vehicle were performed in a novel environment so that only unconditional effects of BSR were affected by the pharmacological manipulations. Subsequently, in a probe test, all rats were returned in the drug-free state to the boxes where they had received training instrumental responding was reassessed in the absence of BSR delivery. LiCl produced enduring decreases in the number of responses during the test session, whereas AM251 had no effect. These results show that instrumental responding for BSR is susceptible to devaluation, in accord with the proposal that this behavior is supported at least in part by associations between the response and the rewarding outcome. Furthermore, they suggest that the reward modulation observed in studies involving the use of CB1 receptor antagonists arises from changes in the organism’s motivation rather than due to drug-induced changes in the intrinsic value of reward.